Pembelajaran Interaktif Bangun Ruang dan Bangun Datar Untuk Sekolah Menengah Pertama (SMP) Berbasis Android - Andreas Sanjaya Putra; Leo Willyanto Santoso; Henry Novianus Palit (Jurnal Infra, 2016)
Two dimensional and three dimensional is part of mathematic that hard to learn if do not know the visualization. Otherwise 2 dimensional and 3 dimensional have to many formulas and a lots of image, so make student hard to learn and to understand.With this problem this application made for educational purpose with 3D visualization using OpenGL ES for geometry, other that this program have calculating the formula’s features, Drawing features, Quiz to help user to understand, and mini game features to help a user does not get bored while learning, but user also can learn and play at the same time.Based on testing result, this application was able to process some kinds of questions and the correct answers, to introducing the material of geometry and plane with visualization, calculate with the right formula, and plane visualization with user interaction.